Biochemical Characterization of a Novel Redox-Regulated Metacaspase in a Marine Diatom - Graff van Creveld, Shiri; Ben-Dor, Shifra; Mizrachi, Avia; Alcolombri, Uria; Hopes, Amanda; Mock, Thomas; Rosenwasser, Shilo; Vardi, Assaf (Frontiers in Microbiology, 2021)
Programmed cell death (PCD) in marine microalgae was suggested to be one of the mechanisms that facilitates bloom demise, yet its molecular components in phytoplankton are unknown. Phytoplankton are completely lacking any of the canonical components of PCD, such as caspases, but possess metacaspases. Metacaspases were shown to regulate PCD in plants and some protists, but their roles in algae and other organisms are still elusive. Here, we identified and biochemically characterized a type III metacaspase from the model diatom Phaeodactylum tricornutum, termed PtMCA-IIIc. Through expression of recombinant PtMCA-IIIc in E. coli, we revealed that PtMCA-IIIc exhibits a calcium-dependent protease activity, including auto-processing and cleavage after arginine. Similar metacaspase activity was detected in P. tricornutum cell extracts. PtMCA-IIIc overexpressing cells exhibited higher metacaspase activity, while CRISPR/Cas9-mediated knockout cells had decreased metacaspase activity compared to WT cells. Site-directed mutagenesis of cysteines that were predicted to form a disulfide bond decreased recombinant PtMCA-IIIc activity, suggesting its enhancement under oxidizing conditions. One of those cysteines was oxidized, detected in redox proteomics, specifically in response to lethal concentrations of hydrogen peroxide and a diatom derived aldehyde. Phylogenetic analysis revealed that this cysteine-pair is unique and widespread among diatom type III metacaspases. The characterization of a cell death associated protein in diatoms provides insights into the evolutionary origins of PCD and its ecological significance in algal bloom dynamics.